Osteochondroma of the mandibular condyle - Ashish Kumar; Sanjay Rastogi; Mancy Modi; Sushil Nijhawan (Indian Journal of Dental Research, 2011)
Osteochondroma (OC) of the mandibular condyle is a relatively rare condition that causes a progressive enlargement of the condyle, usually resulting in facial asymmetry, temporomandibular joint (TMJ) dysfunction, and malocclusion. Radiographically, there is a unilaterally enlarged condyle usually with an exophytic outgrowth of the tumor from the condylar head. We present a case of a left mandibular condylar OC that created a major facial asymmetry, malocclusion, and TMJ dysfunction. Discussion includes the rationale for treatment and the method used in this case. In actively growing OCs, surgical intervention is indicated to remove the tumor stopping the benign growth process and improve facial symmetry, occlusion, and jaw function.